Rising BMI is Associated with Increased Rate of Clinically Relevant Pancreatic Fistula after Distal Pancreatectomy for Pancreatic Adenocarcinoma. Issue 12 (December 2019) - Zhou, Yixuan; Drake, Justin; Deneve, Jeremiah L.; Behrman, Stephen W.; Dickson, Paxton V.; Shibata, David; Glazer, Evan S.
Clinically relevant pancreatic fistula (CR-POPF), after distal pancreatectomy (DP), remains a clinical challenge. Prior studies investigating the relationship between BMI and CR-POPF have yielded conflicting results. We hypothesized that BMI is associated with CR-POPF in patients having DP for pancreatic ductal adenocarcinoma (PDAC). Patients who underwent DP for PDAC at a single institution from 2006 to 2018 were retrospectively reviewed. A CR-POPF was defined as International Study Group of Pancreatic Surgery (ISGPS) grade B or C fistula. Uni- and multivariable logistic regression analysis assessed factors associated with CR-POPF after DP. Seventy-eight patients met the inclusion criteria, 51 per cent were female, 51 per cent were white, and the average age was 59 ± 15 years. The median BMI was 26 (IQR 24–29). Of all, 19 per cent (n = 15) of patients had a CR-POPF. With a mean follow-up of 2.8 ± 2.5 years, the presence of a CR-POPF was not associated with survival ( P = 0.17). On univariable logistic regression, older age was associated with a decreased risk of CR-POPF (odds ratio (OR) = 0.95, P = 0.015). Increasing BMI was associated with an increased risk of CR-POPF (OR = 1.1, P = 0.044). On multivariate analysis, after controlling for multiple factors, BMI (OR = 1.12, P = 0.035) was the only factor associated with the development of a CR-POPF, whereas older age (OR = 0.94, P < 0.001) was slightly protective. Increasing BMI is associated with an increased risk of CR-POPF after DP for PDAC. These findings should be considered during preoperative counseling. Efforts to diminish the risk of CR-POPF should be focused on patients with higher BMI.